The Phenomena of Part-Time Work for Students of Unnes (Journal of Economic Education, 2022)
Part-time work done by students focuses more on personality growth and development, mental development, social interaction, maturity in thinking, and creativity. The objective of this study is to find out and analyze the factors that make Unnes students choose to work part-time while still studying. This study was a descriptive study with mix method approach of the Sequential Exploratory model. The subjects of this research were Unnes students who work part-time in the Unnes Sekaran campus environment or students who have businesses. Data collection was done by using questionnaires. Data analysis was performed by factor analysis and descriptive data analysis. The results showed that there were five factors that cause Unnes students to work part-time namely work readiness, entrepreneurial interest, individual characteristics, relationships and work experience, as well as routine and job characteristics.